Management of Okra Powdery Mildew Through Fungicides (Journal of Plant Disease Sciences, 2019)
Powdery mildew (Erysiphe cinchoracearum Dc) is one of the most important disease infecting okra (Abelmoschus esculentum (L) Moench) leading to low yield and ultimately resulting in economic losses especially during warm and dry weather conditions. From the four years of experimentation it was concluded that the maximum disease reduction (54.50%) was recorded in three foliar sprays of propiconazole 25 EC. @0.1% followed by penconazole 10 EC@ 0.1% and difenconazole 25EC@ 0.1% recording 44.80% and 44.32% respectively. Sprays of wettable sulphur 80 WP @ 0.25% recorded percent disease reduction over control was up to 33.86%. Maximum yield was noticed in the treatment of propiconazole recording 63.16 q/h okra fruits followed by difenconazole exhibiting 55.02 q/h Maximum ICBR (17.51) was observed in wettable sulphur followed by propiconazole (14.32).
Keywords: Okra; Erysiphe cichoracearum; Cost benefit ratio; Chemicals